Health services provision and decision to buy Jaminan Kesehatan Nasional (JKN) in Indonesia - Khoirunurrofik Khoirunurrofik; Giani Raras (Health Policy Open, 2021)
The biggest challenge for the Indonesian government in implementing Universal Health Coverage (UHC) is the coverage of Jaminan Kesehatan Nasional (JKN) owners, which is targeted to reach a minimum of 95%. The study examines whether there are associations between the availability of health care services and the willingness to pay (WTP) for the premium health insurance of non-low-income independent workers. Using a pooled cross-sectional study of 1.054.779 people living above the poverty line based on the 2017–2020 National Economic Survey (SUSENAS) published by the Central Statistics Agency, we investigate the role of supply side factors of health services on individual decisions to own JKN deploying the logistic regression. The WTP for JKN participation will increase if additional supplies of health facilities, beds, and doctors in hospitals are provided. The finding of the study indicates that the availability of health services in the hospital represents service qualities and will influence someone to attain JKN. Additionally, the availability of Community Health Centres (CHCs) and doctors in CHCs will affect people’s behaviour and decision to purchase health insurance due to the existing primary health care facilities in every sub-district across Indonesia. This implies that the government is obliged to afford adequate health care facilities and providers both in urban and rural areas regardless of the level of WTP citizens.